The impact of 12C6 heavy ion irradiation-induced cellular mutations on the replication of the foot-and-mouth disease virus and the role of Cbr3 - Xiangdong Song; Shiyu Tao; Fanglan An; Xiaoming Li; Yanyan Chang; Xuerong Liu; Yan Cui (Cellular and Molecular Life Sciences, 2025)
Abstract Foot-and-mouth disease (FMD) is an infectious disease in animals caused by the foot-and-mouth disease virus (FMDV). However, the mechanism of FMDV infection in host cells remains unclear. In this study, we utilized 12C6 heavy ion irradiation technology to process BHK-21 cells and systematically screened and evaluated cell lines with distinct virus replication characteristics. We subsequently employed proteomics to detect the differences between these cell lines and the control BHK-21 cell line following 12C6 heavy ion irradiation. Both cell lines exhibited common downregulation of cell adhesion molecules but also exhibited distinct upregulation pathways. In terms of immune and metabolic responses, BHK-5 infection triggered an immune response, including the upregulation of cytokine–cytokine receptor signaling pathways and lysosome-related pathways, while the upregulation of drug metabolism pathways enhanced the ability to metabolize exogenous substances. Conversely, BHK-7 infection tended to promote metabolic pathway changes that favor virus replication, such as the upregulation of folate biosynthesis, polysaccharide degradation, and linolenic acid metabolism pathways. Additionally, we observed significant downregulation of Cbr3 in cell lines that promoted virus replication and significant upregulation in those that inhibited virus replication. Upon validating the results in Cbr3 knockout cells, we found that knocking out Cbr3 could increase FMDV replication by increasing the cellular content of prostaglandin E2 (PGE2), suggesting a close relationship between FMDV replication and PGE2 levels. This method can increase the production efficiency of FMDV vaccines while reducing manufacturing costs. This study innovatively employed 12C6 heavy ion irradiation technology to induce cell transformation and explored its impact on FMDV, offering a new perspective for understanding virus replication mechanisms and potentially providing a target and idea for developing novel antiviral strategies.